Multimodal physiotherapeutic approach: effects on the temporomandibular disorder diagnosis and severity - Ariane Bôlla Freire; Angélica Trevisan De Nardi; Jalusa Boufleur; Laís Chiodelli; Fernanda Pasinato; Eliane Castilhos Rodrigues Corrêa
Introduction The temporomandibular disorder (TMD) consists of a set of signs and symptoms that affect the masticatory structures, which may cause joint and/or muscular pain. The physiotherapy approach aims at the pain relief and the functional recovery by means of several modalities.Objective To investigate the effects, short and medium-term, of a multimodal physiotherapeutic approach on TMD diagnosis and severity.Methodology Individuals with diagnosis of TMD, confirmed by the Axis I of the RDC/TMD, took part in the study. From this evaluation, the Temporomandibular Index (TMI) and its sub-indices were calculated. The participants were treated during ten sessions of physiotherapy, which included therapeutic ultrasound, thermotherapy, manual therapy, stretching and neuromuscular exercises, as well as self-care and home exercises instructions. Assessments were carried out before treatment (AV1), immediately after treatment (AV2) and two months after the end of the treatment (AV3). The values of indices and the diagnosis prevalence were compared between the different periods by the t paired test (p < 0.05).Results The number of diagnoses reduced in all the subgroups and 41.7% of the 24 participants presented no diagnosis after the treatment. A significant decrease in the TMI was observed between AV1 and AV2 (p = 0.000). There was no difference between AV2 and AV3 (p = 0.204) in 13 participants assessed two months after the end of the treatment.Conclusion The multimodal physiotherapeutic approach resulted in positive effects, short and medium-term, on the symptoms and clinical signs, with deletion of the dysfunction or reduction of its severity in treated patients.